The control of counterfeit medicine in Malaysia by pharmaceutical enforcement division / Noraimi Ngarip - Noraimi, Ngarip (2010)
This research provided an overview of the control of counterfeit medicine in Malaysia Counterfeit medicine is a major concern due to its impact on the public health, healthcare system, economics and the country at large. This study outlined and described existing methods to curb counterfeit medicine in Malaysia as employed by the Pharmaceutical Enforcement Division, Ministry of Health, with an evaluation of current responses towards counterfeit medicine and suggestions of suitable improvements in the methods of preventing availability of counterfeit medicines. Library-based research and semi-structured interviews were conducted to collect all relevant information during the research. This study revealed a lack of definition and specific provision on counterfeit medicine in existing legislations. The current laws may be able to control the counterfeit medicine to some extent but are not sufficiently comprehensive due to some weaknesses which need to be remedied. The weaknesses of the laws should be reviewed and resolved by the government. This study further recommended the steps that the authority and policy makers should look into to tackle the counterfeit medicine problems. Recommendations from this research might not be final, but it can be useful in assisting the policy makers to implement laws, policies and standards on the issues.